Cultural Diversity in Western Asia: Econometric Modeling of Trust and Ranking by Homogeneity - Alhanaqtah, Omar Jraid Mustafa (Asian Journal of Economic Modelling, 2018)
The main objective of the research is to discover Western Asian countries in the dimensions of new institutional economics: ethnicity, language, religion and trust. The region significantly overlaps with the Middle East which is growing in population terms. It makes mentioned issues interesting for discussion. In order to evaluate a relationship between 'Ethnicity and Trust', "Language and Trust' and 'Religion and Trust' a correlation and regression analysis is conducted. The author also makes an attempt to determine the influence of these three independent variables on the dependent variable 'Trust'. Additionally, a new complex estimator, consisting of 'Ethnicity', "Language' and 'Religion' fragmentation indices, was created and computed. The complex estimator allows to evaluate cultural diversity of the region - homogeneity or heterogeneity - in terms of ethnicity, language and religion simultaneously, as well as to determine the most trustful societies. Business agents may base their investment-location decisions on the complex estimator as an additional informational criterion of risk reduction.